Wafer scale fabrication of graphene microelectrode arrays for the detection of DNA hybridization - Campos, R. (2018)
Since the discovery of graphene, and due to its unique properties, we have witnessed a growing interest in the use of graphene-based devices for applications in the most diverse areas, namely in biosensing, particularly in the detection of genetic material. DNA can bind directly to graphene without the need of a linker and that makes this platform highly interesting for biosensor development. Here, electrochemical chips consisting of 6 independent gold microelectrode arrays as working electrode, and platinum reference and counter electrodes were fabricated at the wafer scale and, after graphene transfer and patterning, were used in the detection of DNA hybridization. Combining the sensitivity of electrochemical impedance spectroscopy and the selectivity of DNA beacons, we were able to detect DNA hybridization in a linear range between 5 pM and 5 nM, which is in the relevant clinical range for many diseases, with sensitivity to single nucleotide polymorphism.